Handling environmental values in product assessments: voices from practice. (6th June 2005) - Bengtsson, Magnus; Tillman, Anne-Marie
Many life cycle assessments include weighting of environmental impacts. The way these trade-offs are handled affects to what extent an assessment leads to relevant and convincing results. To explore reactions to weighting, group interviews with representatives of Swedish authorities, industrial and public purchasing departments, an environmental nongovernmental organisation and research bodies were carried out. We conclude that support for study outcomes can best be reached through improved capacity to handle and communicate value differences. The findings suggest that weighting approaches that can accommodate different perspectives, such as panels, may be more effective. The study also revealed that the need to handle value choices in assessments is often poorly understood. This might impede effective assessments since there is a risk of value vacuums, situations where no one takes responsibility for setting environmental priorities.